A method for preparing a high-strength aluminum nitride ceramic substrate
Patent Information
- Application Number
- CN202410329258.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-03-21
AI Technical Summary
[0004]为了提高氮化铝陶瓷基板的力学性能差的问题,本申请提供了一种高强度氮化铝陶瓷基板的制备方法
1、本申请中改性氮化铝粉体具有良好的导热性和绝缘性能,烧结助剂、氮化铝粉体与有机溶剂混合,使得三者混合更充分更均匀,得到成分均匀的改性氮化铝粉体,有机溶剂使得烧结助剂和氮化铝粉体混合更充分,增强了烧结助剂和氮化铝粉体之间的相互作用;同时烧结助剂在后续改性氮化铝粉体烧结过程中产生液相,促进氮化铝胚体的致密烧结。
Smart Images

Figure BDA0004752976050000081 
Figure BDA0004752976050000091
Abstract
Description
Technical Field
[0001] This application relates to the technical field of ceramic materials, and in particular to a method for preparing a high-strength aluminum nitride ceramic substrate. Background Technology
[0002] Aluminum nitride (AlN) ceramics possess excellent physical and chemical properties such as thermal conductivity, heat resistance, thermal shock resistance, and electrical insulation. They are also non-toxic, and their coefficient of thermal expansion is similar to that of silicon (Si). As such, they are an ideal substrate material for high-density electronic packaging and have great application prospects in the field of LED lighting.
[0003] In the existing technology, the preparation method of aluminum nitride ceramic substrate usually involves mixing aluminum nitride powder, sintering agent, dispersant and solvent, and then grinding, casting, debinding and sintering to obtain aluminum nitride substrate. However, the mechanical properties of the produced aluminum nitride ceramic substrate are not good, with low bending strength and fracture toughness. Summary of the Invention
[0004] To address the issue of poor mechanical properties in aluminum nitride ceramic substrates, this application provides a method for preparing high-strength aluminum nitride ceramic substrates.
[0005] This application provides a method for preparing a high-strength aluminum nitride ceramic substrate, using the following technical solution: A method for preparing a high-strength aluminum nitride ceramic substrate includes the following steps: (1) Mix modified aluminum nitride powder, sintering aid and organic solvent, and ball mill once for 12-24 hours. Then dry to obtain powder. (2) Then the powder obtained in step (1), modified ethyl cellulose and dispersant are mixed and ball-milled for 12-24 hours. Then vacuum degassing is performed to obtain ceramic slurry. (3) The ceramic slurry obtained in step (2) is cast into a green strip, which is then sliced, stacked, debonded, and sintered to obtain a high-strength aluminum nitride ceramic substrate.
[0006] By adopting the above technical solution, the modified aluminum nitride powder has good thermal conductivity and insulation properties. The sintering aid, aluminum nitride powder and organic solvent are mixed to make the three more fully and uniformly mixed, resulting in modified aluminum nitride powder with uniform composition. The organic solvent makes the sintering aid and aluminum nitride powder mix more fully and enhances the interaction between the sintering aid and aluminum nitride powder. At the same time, the sintering aid generates a liquid phase during the subsequent sintering process of modified aluminum nitride powder, which promotes the dense sintering of aluminum nitride preform.
[0007] Then, the powder obtained in step (1), modified ethyl cellulose and dispersant are mixed and ball-milled a second time. Modified ethyl cellulose can effectively improve the physical properties of the powder, has good rheological properties, and enhances the interaction force between powder particles, making the powder molding more uniform and dense, and greatly improving the molding quality and efficiency.
[0008] During the grinding process, the dispersant can coexist with the sintering aid and powder particles, reducing the surface tension between the components in the system and increasing the contact area, thereby further improving the grinding effect and resulting in more uniform powder particles. Then, vacuum degassing is performed to remove air bubbles from the ceramic slurry, making the slurry more uniform and dense. Next, it is cast into a green belt of the required thickness, then sliced, stacked, debinded, and sintered to obtain a high-strength, dense aluminum nitride ceramic substrate.
[0009] Preferably, the sintering aid is a mixture of CaO, SrO and Y2O3 in a mass ratio of 1:0.7-0.9:1.7-2.1.
[0010] By adopting the above technical solution, CaO, SrO, and Y2O3, as sintering aids, exhibit strong catalytic activity and the ability to lower sintering temperature during the sintering process, promoting sintering, increasing the density of aluminum nitride, and reducing production efficiency. Y2O3 also reduces the lattice oxygen content of aluminum nitride during sintering, improving the thermal conductivity of the aluminum nitride ceramic substrate. The appropriate mass ratio of CaO, SrO, and Y2O3 effectively inhibits the growth of aluminum nitride crystals, resulting in uniform grain size, tight grain bonding, and high strength. The liquid-phase reaction between CaO, SrO, Y2O3, and the aluminum nitride surface provides a liquid phase for aluminum nitride crystal growth while simultaneously reducing the oxygen content of the aluminum nitride crystals, forming high-strength, high-thermal-conductivity aluminum nitride grains. The combined effect of these components lowers the sintering temperature of the system, facilitating the sintering of aluminum nitride and increasing its density.
[0011] Preferably, the method for preparing the modified aluminum nitride powder includes the following steps: dispersing aluminum nitride powder in hydrochloric acid, stirring for 10-15 min, washing with water, then dispersing in deionized water, stirring at 65-70℃ for 20-25 min, then sequentially adding silane coupling agent, modified nano nickel and stearic acid, stirring for 2-4 h, filtering and drying to obtain modified aluminum nitride powder.
[0012] By employing the above technical solutions, hydrochloric acid removes organic impurities from aluminum nitride powder, increasing its porosity and specific surface area. Silane coupling agents modify the surface of aluminum nitride powder, further improving its dispersibility and compatibility with other components, thus facilitating uniform dispersion. Modified nano-nickel possesses high hardness, excellent thermal conductivity, and strength, enabling it to be loaded onto the surface and pores of aluminum nitride powder, thereby enhancing its strength and mechanical properties. Stearic acid further reduces the viscosity of the system, preventing particle agglomeration and improving particle dispersion. Simultaneously, stearic acid allows the silane coupling agent to disperse more evenly in deionized water, facilitating better reaction between the aluminum nitride powder and the silane coupling agent, effectively improving the strength and dispersibility of the aluminum nitride powder, which in turn contributes to improving the corresponding performance of the ceramic substrate.
[0013] Preferably, the mass ratio of the aluminum nitride powder, silane coupling agent, modified nano nickel, and stearic acid is 1:0.2-0.4:0.6-0.8:0.1-0.3.
[0014] By adopting the above technical solution, the mass ratio of aluminum nitride powder, silane coupling agent KH550, modified nano-nickel, and stearic acid is further limited within a certain range, thereby improving the corresponding properties of aluminum nitride powder. The silane coupling agent modifies the aluminum nitride powder, improving its dispersibility. The modified nano-nickel is loaded on the surface and within the pores of the aluminum nitride powder, improving its hardness, thermal conductivity, and strength. Stearic acid allows the silane coupling agent to be better and more uniformly dispersed in deionized water, resulting in better mixing of aluminum nitride powder, silane coupling agent, and modified nano-nickel, improving the strength and dispersibility of the aluminum nitride powder, which helps to improve the corresponding properties of the ceramic substrate in the future.
[0015] Preferably, the method for preparing the modified nickel nanoparticles includes the following steps: dispersing nickel nanoparticles in an acetic acid solution of chitosan, sonicating for 1-2 hours, then adding carbon nanotubes, continuing sonication for 3-5 hours, and drying to obtain modified nickel nanoparticles.
[0016] By adopting the above technical solution, chitosan and nickel nanoparticles are mixed, allowing chitosan to be adsorbed onto the surface of nickel nanoparticles. Carbon nanotubes are then added, further adsorbing onto the chitosan surface to form a stable modified nickel nanoparticle system. This improves the hardness, strength, and adsorption properties of the nickel nanoparticles. When subsequently applied to the preparation method of modified aluminum nitride powder, the corresponding properties of the system are improved, which helps to further enhance the dispersibility and strength of the modified aluminum nitride powder.
[0017] Preferably, the particle size distribution of the aluminum nitride powder, based on mass fraction, includes: 0.02-0.15μm 15.17-17.89%; 0.15-0.35μm 16.22-18.11%; 0.35-0.95μm 19.13-20.41%; 0.95-1.85μm 21.52-23.81%; 1.85-2.35μm 22.72-24.93%.
[0018] By adopting the above technical solution and selecting aluminum nitride powder of different particle sizes, the aluminum nitride powder can be better mixed with sintering aids, binders, etc., thereby increasing the raw material density of subsequent slurry casting or dry pressing, and improving the strength and density of ceramic substrates.
[0019] Preferably, the method for preparing the modified ethyl cellulose includes the following steps: dispersing ethyl cellulose in anhydrous ethanol, stirring at a temperature of 45-55℃ for 25-30 min, then adding glycerol and cellulose acetate butyrate, and continuing to stir for 2-3 h to obtain modified ethyl cellulose.
[0020] By adopting the above technical solution, ethyl cellulose has good dispersibility and flowability, while glycerol has certain viscosity and wettability. When mixed with ethyl cellulose, the wettability of ethyl cellulose is increased. Subsequently, when mixed with aluminum nitride powder, dispersant and other components, the wettability of the system is improved, and the probability of cracking and crazing is reduced. Cellulose acetate butyrate has excellent moisture resistance, UV resistance, flexibility, transparency and electrical insulation properties, and has good compatibility with ethyl cellulose and glycerol. Adjusting the adhesion of the system and improving the dispersibility of ethyl cellulose is helpful for the subsequent application of modified ethyl cellulose in aluminum nitride powder, so that the modified ethyl cellulose can improve the dispersibility and wettability of the system.
[0021] Preferably, the mass ratio of ethyl cellulose, glycerol and cellulose acetate butyrate is 1:0.2-0.3:0.5-0.7.
[0022] By adopting the above technical solution, the mass ratio of ethyl cellulose, glycerol, and cellulose acetate butyrate is further limited within a certain range, thereby improving the dispersibility of ethyl cellulose. Ethyl cellulose, glycerol, and cellulose acetate butyrate have a synergistic effect. Glycerol improves the wettability of ethyl cellulose, and cellulose acetate butyrate improves the dispersibility of ethyl cellulose. This allows the modified ethyl cellulose to be applied to aluminum nitride powder, improving the dispersibility and wettability of the system, which is beneficial for subsequent grinding.
[0023] Preferably, the organic solvent is a mixture of linseed oil, polyethylene wax, and polyethylene glycol in a mass ratio of 1:2-3:5-9.
[0024] By adopting the above technical solution, the organic solvent allows the sintering aid and aluminum nitride powder to mix more thoroughly. Flaxseed oil, polyethylene wax, and polyethylene glycol are mixed in a certain mass ratio as the organic solvent for aluminum nitride powder, which makes the components in the system evenly dispersed, which helps to better grind the aluminum nitride powder and improve the grinding quality and grinding efficiency of the aluminum nitride powder.
[0025] Preferably, the dispersant is a mixture of sodium polyacrylate and fish oil in a mass ratio of 1:5-8.
[0026] By adopting the above technical solution, the dispersant is made by mixing sodium polyacrylate and fish oil in a certain mass ratio, which makes the sintering agent powder particles uniformly mixed during the grinding process, reduces the surface tension between the components in the system, increases the contact area, and thus further improves the grinding effect of the system, resulting in more uniform powder particles.
[0027] In summary, this application has the following beneficial effects: 1. The modified aluminum nitride powder in this application has good thermal conductivity and insulation properties. The sintering aid, aluminum nitride powder and organic solvent are mixed to make the three more fully and uniformly mixed, resulting in modified aluminum nitride powder with uniform composition. The organic solvent makes the sintering aid and aluminum nitride powder mix more fully and enhances the interaction between the sintering aid and aluminum nitride powder. At the same time, the sintering aid generates a liquid phase during the subsequent sintering process of modified aluminum nitride powder, which promotes the dense sintering of aluminum nitride preform.
[0028] 2. In this application, the powder, modified ethyl cellulose, and dispersant are mixed and subjected to secondary ball milling. Modified ethyl cellulose can effectively improve the physical properties of the powder, has better rheological properties, and enhances the interaction force between powder particles, making the powder molding more uniform and dense, and greatly improving the molding quality and efficiency. Modified ethyl cellulose also has good sintering performance. During sintering, it can provide carbonaceous material to form a matte oxide film, which enhances the hardness and density of the ceramic substrate, thereby improving the thermal stability and mechanical properties of the ceramic substrate.
[0029] 3. In this application, the dispersant can coexist with the sintering aid and powder particles during the grinding process, which reduces the surface tension between the components in the system and increases the contact area, thereby further improving the grinding effect of the system and obtaining more uniform powder particles. Then, vacuum degassing is performed to remove air bubbles in the ceramic slurry, making the ceramic slurry more uniform and dense, and obtaining a high-strength, dense aluminum nitride ceramic substrate. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the embodiments.
[0031] The raw materials used in the examples and comparative examples are all commercially available.
[0032] Preparation example of modified aluminum nitride powder Preparation Example 1-1 The preparation method of modified aluminum nitride powder includes the following steps: 1.3 kg of aluminum nitride powder is dispersed in 2 L of 20% hydrochloric acid, stirred for 12 min, washed with water, then dispersed in 2.3 L of deionized water, stirred at 70℃ for 23 min, then silane coupling agent KH550, modified nano nickel and stearic acid are added in sequence, stirred for 3 h, filtered and dried to obtain modified aluminum nitride powder.
[0033] The mass ratio of aluminum nitride powder, silane coupling agent KH550, modified nano nickel, and stearic acid is 1:0.2:0.6:0.1.
[0034] The method for preparing modified nickel nanoparticles includes the following steps: 1.2 kg of nickel nanoparticles are dispersed in an acetic acid solution of chitosan, sonicated for 2 hours, then 0.3 kg of carbon nanotubes are added, and sonication continues for 5 hours. The mixture is then dried to obtain modified nickel nanoparticles. The acetic acid solution of chitosan is prepared by dissolving 0.5 kg of chitosan in 1.3 L of acetic acid solution.
[0035] The particle size distribution of aluminum nitride powder, expressed as a mass fraction, includes: 0.02-0.15μm 16.22%; 0.15-0.35μm 17.11%; 0.35-0.95μm 19.13%; 0.95-1.85μm 23.56%; 1.85-2.35μm 23.98%.
[0036] Preparation Examples 1-2 The difference from Preparation Example 1-1 is that the silane coupling agent KH550 is not added.
[0037] Preparation Examples 1-3 The difference from Preparation Example 1-1 is that no modified nano-nickel is added.
[0038] Preparation Examples 1-4 The difference from Preparation Example 1-1 is that stearic acid is not added.
[0039] Preparation Examples 1-5 The difference from Preparation Example 1-1 is that the mass ratio of aluminum nitride powder, silane coupling agent KH550, modified nano nickel and stearic acid is 1:0.4:0.8:0.3.
[0040] Preparation Examples 1-6 The difference from Preparation Example 1-1 is that the mass ratio of aluminum nitride powder, silane coupling agent KH550, modified nano nickel and stearic acid is 1:0.7:0.2:0.4.
[0041] Preparation Examples 1-7 The difference from Preparation Example 1-1 is that chitosan is not added in the preparation method of modified nickel nanoparticles.
[0042] Preparation Examples 1-8 The difference from Preparation Example 1-1 is that carbon nanotubes are not added in the preparation method of modified nickel nanoparticles.
[0043] Preparation example of modified ethyl cellulose Preparation Example 2-1 The preparation method of modified ethyl cellulose includes the following steps: 1.5 kg of ethyl cellulose is dispersed in 1.8 L of anhydrous ethanol, stirred at 55 °C for 30 min, then glycerol and cellulose acetate butyrate are added, and stirring is continued for 3 h to obtain modified ethyl cellulose.
[0044] The mass ratio of ethyl cellulose, glycerol, and cellulose acetate butyrate is 1:0.2:0.5.
[0045] Preparation Example 2-2 The difference from Preparation Example 2-1 is that glycerol is not added.
[0046] Preparation Examples 2-3 The difference from Preparation Example 2-1 is that cellulose acetate butyrate is not added.
[0047] Preparation Examples 2-4 The difference from Preparation Example 2-1 is that the mass ratio of ethyl cellulose, glycerol and cellulose acetate butyrate is 1:0.3:0.7.
[0048] Preparation Examples 2-5 The difference from Preparation Example 2-1 is that the mass ratio of ethyl cellulose, glycerol and cellulose acetate butyrate is 1:0.6:0.2. Example
[0049] Example 1 A method for preparing a high-strength aluminum nitride ceramic substrate includes the following steps: (1) Mix 9.8 kg of modified aluminum nitride powder, 0.6 kg of sintering aid and 4.5 kg of organic solvent, and ball mill once for 14 h. Then dry to obtain powder. (2) Then mix the powder obtained in step (1), 1.5 kg of modified ethyl cellulose and 0.2 kg of dispersant, and ball mill for 22 h. Then vacuum degassing is performed to obtain ceramic slurry. (3) The ceramic slurry obtained in step (2) is cast into a green strip, which is then sliced, stacked, debonded, and sintered to obtain a high-strength aluminum nitride ceramic substrate.
[0050] The sintering aid is a mixture of CaO, SrO and Y2O3 in a mass ratio of 1:0.7:2.1.
[0051] The organic solvent is a mixture of linseed oil, polyethylene wax, and polyethylene glycol in a mass ratio of 1:2:9.
[0052] The dispersant is a mixture of sodium polyacrylate and fish oil in a mass ratio of 1:8.
[0053] The ceramic was sintered in a vacuum nitrogen furnace under a nitrogen atmosphere of 9 kp positive pressure, at a temperature of 1820℃, for a high-temperature sintering time of 5 hours.
[0054] The degassing process was carried out under vacuum conditions at a temperature of 540℃ for 54 hours. Degassing was then performed with a vacuum level controlled at -99.9 PSI, a stirring rate of 1200 r / min, and a degassing time of 35 minutes. The viscosity after degassing was controlled at 4200 MPa·s.
[0055] The thickness of the cast blank is 0.5 mm, and the length and width of each blank are 120 mm. Four blanks are stacked together and isostatically pressed for 36 minutes under a pressure of 100 MPa and a temperature of 80℃. The specific conditions for this casting process are: blade height of 0.5 mm, casting rate of 0.6 m / min, and casting heating temperature of 35℃.
[0056] The modified aluminum nitride powder was prepared using Preparation Example 1-1, and the modified ethyl cellulose was prepared using Preparation Example 2-1.
[0057] Example 2 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the sintering aid is a mixture of CaO, SrO and Y2O3 in a mass ratio of 1:0.9:1.7.
[0058] The organic solvent is a mixture of linseed oil, polyethylene wax, and polyethylene glycol in a mass ratio of 1:3:5.
[0059] The dispersant is a mixture of sodium polyacrylate and fish oil in a mass ratio of 1:5.
[0060] Example 3 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified aluminum nitride powder is prepared using Preparation Examples 1-2.
[0061] Example 4 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified aluminum nitride powder is prepared using Preparation Examples 1-3.
[0062] Example 5 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified aluminum nitride powder is prepared using Preparation Examples 1-4.
[0063] Example 6 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified aluminum nitride powder is prepared using Preparation Examples 1-5.
[0064] Example 7 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified aluminum nitride powder is prepared using Preparation Examples 1-6.
[0065] Example 8 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified aluminum nitride powder is prepared using Preparation Examples 1-7.
[0066] Example 9 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified aluminum nitride powder is prepared using Preparation Examples 1-8.
[0067] Example 10 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified ethyl cellulose is prepared using Preparation Example 2-2.
[0068] Example 11 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified ethyl cellulose is prepared using Preparation Examples 2-3.
[0069] Example 12 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified ethyl cellulose is prepared using Preparation Examples 2-4.
[0070] Example 13 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that the modified ethyl cellulose is prepared using Preparation Examples 2-5.
[0071] Comparative Example Comparative Example 1 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that an equal amount of aluminum nitride powder is used instead of modified aluminum nitride powder.
[0072] Comparative Example 2 A method for preparing a high-strength aluminum nitride ceramic substrate differs from Example 1 in that an equal amount of ethyl cellulose is used instead of modified ethyl cellulose.
[0073] Performance testing Performance tests were conducted according to the preparation processes of Examples 1-13 and Comparative Examples 1-2: The relative density of the high-strength aluminum nitride ceramic substrates in the examples and comparative examples was tested according to the standard GB / T 25995-2010 test method for density and apparent porosity of fine ceramics. The flexural strength and fracture toughness of the high-strength aluminum nitride ceramic substrates in the examples and comparative examples were tested according to GB / T 6569-2006, Test Method for Bending Strength of Fine Ceramics. The warping of high-strength ceramic substrates was measured using a parallel plate warping tester. The standard spacing between the parallel plates was equal to the standard thickness of the substrate plus the allowable warping value (1.8‰). The ceramic substrate was considered to be qualified for warping if it passed between the parallel plates. The test results are shown in Table 1.
[0074] Table 1 Test data for the examples and comparative examples As can be seen from Table 1, the high-strength aluminum nitride ceramic substrates prepared in Examples 1-2, 6, and 12 of this application exhibit good strength. Specifically, in Example 1, the prepared ceramic substrate has a relative density of 99.8%, a flexural strength of 498 MPa, and a fracture toughness of 3.97 MPa / m². 1 / 2 The warpage is 1.01‰, indicating that the components of this application work together to obtain a high-strength, dense aluminum nitride ceramic substrate.
[0075] In Example 3, the modified aluminum nitride powder was prepared without the addition of silane coupling agent KH550. As shown in Table 1, compared to Example 1, the prepared ceramic substrate had a relative density of 97.8%, a flexural strength of 486 MPa, and a fracture toughness of 3.85 MPa / m². 1 / 2 The warpage was 1.12‰. This indicates that the silane coupling agent modified the surface of the aluminum nitride powder, further improving the dispersibility of the aluminum nitride powder, enhancing its compatibility with other components, and contributing to the uniform dispersion of the aluminum nitride powder with other components.
[0076] In Example 4, the preparation method of modified aluminum nitride powder did not include modified nano-nickel. As shown in Table 1, compared with Example 1, the prepared ceramic substrate had a relative density of 95.1%, a flexural strength of 472 MPa, and a fracture toughness of 3.66 MPa / m. 1 / 2The warpage was 1.33‰. This indicates that the modified nano-nickel can be loaded onto the surface and within the pores of aluminum nitride powder, thereby improving the strength and mechanical properties of the aluminum nitride powder.
[0077] In Example 5, the preparation method of modified aluminum nitride powder did not include stearic acid. As shown in Table 1, compared with Example 1, the prepared ceramic substrate had a relative density of 98.4%, a flexural strength of 490 MPa, and a fracture toughness of 3.90 MPa / m. 1 / 2 The warpage was 1.08‰. This indicates that stearic acid further reduces the viscosity of the system, prevents particle agglomeration, and improves particle dispersion. At the same time, stearic acid can better and more evenly disperse the silane coupling agent in deionized water, allowing the aluminum nitride powder to react better with the silane coupling agent, thereby effectively improving the strength and dispersibility of the aluminum nitride powder.
[0078] Example 7 changed the mass ratio of aluminum nitride powder, silane coupling agent KH550, modified nano-nickel, and stearic acid. As shown in Table 1, compared with Example 1, the flexural strength, fracture toughness, and warpage performance of the prepared ceramic substrate were better than those of Examples 3-5, but worse than those of Examples 1 and 6. This indicates that the modified nano-nickel loaded on the surface and in the pores of the aluminum nitride powder improved the hardness, thermal conductivity, and strength of the aluminum nitride powder. The stearic acid enabled the silane coupling agent to be better and more uniformly dispersed in deionized water, resulting in better mixing of aluminum nitride powder, silane coupling agent, and modified nano-nickel, improving the strength and dispersibility of the aluminum nitride powder, which helps to improve the corresponding performance of the ceramic substrate in the future.
[0079] In Example 8, the preparation method of modified nano-nickel did not include chitosan. As shown in Table 1, compared with Example 1, the prepared ceramic substrate had a relative density of 96.2%, a flexural strength of 480 MPa, and a fracture toughness of 3.73 MPa / m. 1 / 2 The warpage was 1.21‰. This indicates that chitosan can be adsorbed onto the surface of nickel nanotubes, increasing the adhesion between carbon nanotubes and nickel nanotubes, thereby improving the strength of nickel nanotubes and subsequently improving the dispersibility and strength of modified aluminum nitride powder.
[0080] In Example 9, the method for preparing modified nano-nickel did not include carbon nanotubes. As shown in Table 1, compared to Example 1, the prepared ceramic substrate had a relative density of 95.9%, a flexural strength of 476 MPa, and a fracture toughness of 3.71 MPa / m. 1 / 2 The warpage was 1.28‰. This indicates that the addition of carbon nanotubes allowed them to be further adsorbed onto the chitosan surface, forming a stable modified nickel nanoparticle system, which improved the hardness, strength, and adsorption properties of the nickel nanoparticles.
[0081] In Example 10, the preparation method of modified ethyl cellulose did not include glycerol. As shown in Table 1, compared with Example 1, the prepared ceramic substrate had a relative density of 97.2%, a flexural strength of 483 MPa, and a fracture toughness of 3.81 MPa / m. 1 / 2 The warpage was 1.16‰. This indicates that glycerol has certain viscosity and wettability. When mixed with ethyl cellulose, it increases the wettability of ethyl cellulose. Subsequently, when mixed with aluminum nitride powder, dispersants, and other components, it further improves the wettability of the system and reduces the probability of cracking and crazing.
[0082] In Example 11, the preparation method of modified ethyl cellulose did not include cellulose acetate butyrate. As shown in Table 1, compared with Example 1, the prepared ceramic substrate had a relative density of 96.7%, a flexural strength of 481 MPa, and a fracture toughness of 3.76 MPa / m. 1 / 2 The warpage was 1.19‰. This indicates that cellulose acetate butyrate has excellent moisture resistance, UV resistance, flexibility, transparency, and electrical insulation properties. It also has good compatibility with ethyl cellulose and glycerol, which can adjust the adhesion of the system and improve the dispersibility of ethyl cellulose. This is beneficial for the subsequent application of modified ethyl cellulose in aluminum nitride powder, thereby improving the dispersibility and wettability of the system.
[0083] Example 13 altered the mass ratio of ethyl cellulose, glycerol, and cellulose acetate butyrate. As shown in Table 1, compared to Example 1, the prepared ceramic substrate exhibited superior flexural strength, fracture toughness, and warpage performance compared to Examples 10-11, but inferior performance compared to Examples 1 and 9. This indicates a synergistic effect between ethyl cellulose, glycerol, and cellulose acetate butyrate. Glycerol enhances the wettability of ethyl cellulose, while cellulose acetate butyrate enhances its dispersibility. This allows the modified ethyl cellulose to be applied to aluminum nitride powder, improving the system's dispersibility and wettability, which is beneficial for subsequent grinding.
[0084] Comparative Example 1 used an equal amount of aluminum nitride powder instead of modified aluminum nitride powder. As shown in Table 1, compared to Example 1, the prepared ceramic substrate had a relative density of 84.1%, a flexural strength of 452 MPa, and a fracture toughness of 3.01 MPa / m². 1 / 2 The warpage was 1.68‰. This indicates that the modified aluminum nitride powder prepared in this application has superior performance. When mixed with sintering aids, modified ethyl cellulose, and other components, it enhances the hardness and density of the ceramic substrate, thereby improving the thermal stability and mechanical strength of the ceramic substrate.
[0085] Comparative Example 2 used an equal amount of ethyl cellulose instead of modified ethyl cellulose. As shown in Table 1, compared to Example 1, the prepared ceramic substrate had a relative density of 85.2%, a flexural strength of 454 MPa, and a fracture toughness of 3.12 MPa / m. 1 / 2The warpage was 1.64‰. This indicates that the modified ethyl cellulose prepared in this application has superior performance. Modified ethyl cellulose can effectively improve the physical properties of powder, has better rheological properties, and enhances the interaction force between powder particles, making the powder molding more uniform and dense, and greatly improving the quality and efficiency of ceramic substrates. This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A method for preparing a high-strength aluminum nitride ceramic substrate, characterized in that, Includes the following steps: (1) Mix the modified aluminum nitride powder, sintering aid and organic solvent, and ball mill once for 12-24 hours. Then dry to obtain the powder. (2) Then the powder obtained in step (1), modified ethyl cellulose and dispersant are mixed and ball-milled for 12-24 hours. Then vacuum degassing is performed to obtain ceramic slurry. (3) The ceramic slurry obtained in step (2) is cast into a green belt, which is then sliced, stacked, debonded, and sintered to obtain a high-strength aluminum nitride ceramic substrate. The preparation method of modified aluminum nitride powder includes the following steps: 1.3 kg of aluminum nitride powder is dispersed in 2 L of 20% hydrochloric acid, stirred for 12 min, washed with water, then dispersed in 2.3 L of deionized water, stirred at 70℃ for 23 min, then silane coupling agent KH550, modified nano nickel and stearic acid are added in sequence, stirred for 3 h, filtered and dried to obtain modified aluminum nitride powder; The mass ratio of aluminum nitride powder, silane coupling agent KH550, modified nano-nickel, and stearic acid is 1:0.2:0.6:0.1; The method for preparing modified nickel nanoparticles includes the following steps: 1.2 kg of nickel nanoparticles are dispersed in an acetic acid solution of chitosan, sonicated for 2 h, then 0.3 kg of carbon nanotubes are added, and sonication is continued for 5 h. After drying, modified nickel nanoparticles are obtained. The acetic acid solution of chitosan is prepared by dissolving 0.5 kg of chitosan in 1.3 L of acetic acid solution.
2. The method for preparing a high-strength aluminum nitride ceramic substrate according to claim 1, characterized in that, The sintering aid is a mixture of CaO, SrO and Y2O3 in a mass ratio of 1:0.7-0.9:1.7-2.
1.
3. The method for preparing a high-strength aluminum nitride ceramic substrate according to claim 1, characterized in that, The particle size distribution of the aluminum nitride powder, in terms of mass fraction, includes: 0.02-0.15µm 15.17-17.89%; 0.15-0.35µm 16.22-18.11%; 0.35-0.95µm 19.13-20.41%; 0.95-1.85µm 21.52-23.81%; 1.85-2.35µm 22.72-24.93%。 4. The method for preparing a high-strength aluminum nitride ceramic substrate according to claim 1, characterized in that, The method for preparing the modified ethyl cellulose includes the following steps: dispersing ethyl cellulose in anhydrous ethanol, stirring at 45-55℃ for 25-30 min, then adding glycerol and cellulose acetate butyrate, and continuing to stir for 2-3 h to obtain modified ethyl cellulose.
5. The method for preparing a high-strength aluminum nitride ceramic substrate according to claim 4, characterized in that, The mass ratio of ethyl cellulose, glycerol and cellulose acetate butyrate is 1:0.2-0.3:0.5-0.
7.
6. The method for preparing a high-strength aluminum nitride ceramic substrate according to claim 1, characterized in that, The organic solvent is a mixture of linseed oil, polyethylene wax, and polyethylene glycol in a mass ratio of 1:2-3:5-9.
7. The method for preparing a high-strength aluminum nitride ceramic substrate according to claim 1, characterized in that, The dispersant is a mixture of sodium polyacrylate and fish oil in a mass ratio of 1:5-8.
Citation Information
Patent Citations
Aluminium nitride ceramic substrate, and preparation method thereof
CN107188568A
High-strength aluminum nitride ceramic substrate and preparation method thereof
CN113121244A
Nickel-doped enhanced aluminum nitride ceramic and preparation method thereof
CN116589293A